Canopy-forming algae improve the colonization success of the vermetid reef-builder Dendropoma cristatum (Biondi 1859) on artificial substrates - La Marca, Emanuela Claudia; Ape, Francesca; Rinaldi, Alessandro; Spoto, Marco; Martinez, Marco; Dini, Enrico; Mirto, Simone; Montalto, Valeria (Frontiers in Marine Science, 2024)
Positive interactions among foundation species play a crucial role in achieving and maintaining a good state of the marine environment, enhancing the habitat stability, productivity, and the whole ecosystem functioning. In this regard, macroalgal canopies may affect the biotic and abiotic environmental features, improving the habitat quality for the establishment of other sedentary organisms. In this study, we investigated the effect of intertidal canopy-forming algae on the colonization success of the central-Mediterranean vermetid reef-builder Dendropoma cristatum (Biondi 1859) on artificial substrates produced for reef restoration purposes. An in situ experiment was carried out along the northwestern coast of Sicily during the breeding season of the vermetid snails, by using geopolymer concrete settlement discs with a topographic design to facilitate the vermetid settlement. The discs were placed on the seaward reef rim, underneath the macroalgal canopy, and on adjacent control bare reef areas. The canopy effect on the understory algal colonization and the environmental temperature at the vermetid settlement substrate were also surveyed. After 35 days of field exposure, the vermetid settlement increased by 1.7-fold on the discs underneath the macroalgal canopy compared with that on the bare settlement discs. Moreover, the understory algae showed a higher homogeneity and a lower percent cover on the settlement discs underneath the macroalgal canopy. The peaks of temperature were higher on the bare reef, and the macroalgal canopy also reduced temperature variability under maximum sun irradiance during the diurnal low tides. The vermetid settlement was positively correlated to the canopy cover, which, directly or indirectly, improved the success of colonization of the reef-builder snails on artificial substrates. The deployment of settlement discs where canopy-forming algae are naturally present may facilitate the gardening of vermetid clusters that may be translocated to restock the reef-builder density at degraded areas.